Formation of social cooperation skills in preschool age - Jalolddin Zainobiddinov; Shakhnoza Kholhujayeva (Genius Journals, 2022)
The article analyzes the mental development of preschool children, their school preparation processes, and the difficulties they encounter in adapting to educational activities
Keywords: preparation for school; psyche of preschool children; adaptation to school; confusion